STEM TAPER EQUATION WITH EXTENSIVE APPLICABILITY TO SEVERAL AGE CLASSES OF Pinus taeda L - Téo, Saulo Jorge; Machado, Sebastião do Amaral; Figueiredo Filho, Afonso; Tomé, Margarida (Floresta, 2018)
The aim of this study was to develop stem taper equations for trees of Pinus taeda L. inside and outside bark with extensive applicability to several age classes. Data were obtained from 631 trees of P. taeda, ranging from 4 to 31 years of age, in different stands distributed in several counties of the Midwest region of the state of Santa Catarina, Brazil. The taper models of Biging (1984), Schöpfer (1966), and Kozak et al. (1969) were tested. These models were fitted in their simplest formulation as well as by varying their coefficient linear functions of stand age with the procedure PROC NLIN in the software SAS® University Edition. There were no significant differences in accuracy and precision in the estimates between the simplest formulation of the Schöpfer (1966) model and the variation of its coefficient b linear function of age, and thus, the simplest formulation was chosen. Among all taper models tested, the Schöpfer (1966) model presented greater accuracy and precision to estimate diameters inside and outside bark, throughout the stem of Pinus taeda, in the Midwest region of the state of Santa Catarina, Brazil.